Patient- and Caregiver-Related Factors Associated with Caregiver Assessed Global Deterioration Scale Scoring in Demented Patients. (4th June 2018) - Mougias, Antonios A.; Christidi, Foteini; Kontogianni, Evaggelia; Skaltsounaki, Elena; Politis, Anastasios; Politis, Antonios
Abstract : Background . Informant-based rating scales are widely used in dementia but patients' and caregivers' features influence the final scoring. We aimed to evaluate the role of patient- and caregiver-related factors in a caregiver rated Global Deterioration Scale (GDS) score in a sample of Greek patients with dementia. Methods . We included 194 patients with dementia and 194 caregivers/family relatives; Mini-Mental State Examination (MMSE); Neuropsychiatric Inventory (NPI); Katz Index of Activities of Daily Living (K-IADL) were administered to (a) patients and Center for Epidemiologic Studies-Depression (CES-D) Scale; Zarit Burden Interview (ZBI) to (b) caregivers. Participants' demographics and patients' and caregivers' characteristics were entered into a 3-block regression analysis. Results . The final model explained 55% of the total variance of the caregiver assessed GDS score. The following variables significantly contributed to the final model: MMSE ( β =-0.524); K-IADL ( β = -0.264); ZBI ( β =0.145). Conclusion . We herein confirm the contribution of patients' cognitive and functional status and caregivers' burden in caregiver rated GDS scoring irrespective of demographic-related characteristics.